Hereditary Angioedema: The Importance of Clinical Suspicion and Proper Treatment - Araújo, Ana; Pinto, Joel; Almeida, Paulo; Pinheiro, Beatriz; Morete, Ana (Portuguese Journal Internal Medicine, 2018)
Hereditary angioedema (HAE) is a syndrome characterized by episodic swelling of subcutaneous and submucosal tissues, due to a deficiency or dysfunctionality in functional C1 esterase inhibitor (C1-inh). The authors present a case of a 40 year-old man with a positive family history of HAE, recurrent episodes of abdominal pain, nausea and vomiting. The immunological study revealed low levels of C1-inh and C4 and normal levels of C1q. Acquired angioedema was excluded, making the diagnosis of type 1 HAE. The patient presented several times to the emergency department with severe abdominal pain, diffuse abdominal tenderness with guarding. However, laboratory and imagiologic studies had no alterations. A subcutaneous injection of icatibant was administered with resolution of symptoms. HAE is a rare and potentially fatal disease, mainly during acute attacks. An early diagnosis and a proper treatment are fundamental.